Предмет: Алгебра,
автор: onipkoandrij
довести тотожність (х-3)(х+7)-(х+8)(х-4)=11
Ответы
Автор ответа:
3
Ответ:Тождество верно
Объяснение: (х-3)(х+7)-(х+8)(х-4)=11
x²+4x-21-x²-4x+32=11
11=11
Автор ответа:
2
Ответ:
На фотографії доведено
Приложения:
![](https://files.topotvet.com/i/508/5081675c48b1fcf6112a14a834d3c6d0.jpg)
Похожие вопросы
Предмет: Русский язык,
автор: 134758n
Предмет: Русский язык,
автор: 8468
Предмет: Русский язык,
автор: edgar19774
Предмет: Математика,
автор: вопрос00
Предмет: Информатика,
автор: pobolSM